2018
DOI: 10.1021/acsami.8b17152
|View full text |Cite
|
Sign up to set email alerts
|

Direct, Transfer-Free Growth of Large-Area Hexagonal Boron Nitride Films by Plasma-Enhanced Chemical Film Conversion (PECFC) of Printable, Solution-Processed Ammonia Borane

Abstract: Synthesis of large-area hexagonal boron nitride (h-BN) films for two-dimensional (2D) electronic applications typically requires high temperatures (∼1000 °C) and catalytic metal substrates which necessitate transfer. Here, analogous to plasma-enhanced chemical vapor deposition, a nonthermal plasma is employed to create energetic and chemically reactive states such as atomic hydrogen and convert a molecular precursor film to h-BN at temperatures as low as 500 °C directly on metal-free substratesa process we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…MoS 2 thin films were synthesized by a process which we term plasma-enhanced chemical film conversion (PECFC), similar to that previously reported for h-BN . Ammonium tetrathiomolybdate (ATM, Sigma-Aldrich) was first dissolved in 10 mL of dimethylformamide (DMF, Fisher Scientific) at 0.1 M with 0.1 g of 10000 MW linear polyethylenimine (L-PEI, Sigma-Aldrich) and sonicated at 60 °C for 1 h to completely dissolve the polymer.…”
Section: Methodsmentioning
confidence: 99%
“…MoS 2 thin films were synthesized by a process which we term plasma-enhanced chemical film conversion (PECFC), similar to that previously reported for h-BN . Ammonium tetrathiomolybdate (ATM, Sigma-Aldrich) was first dissolved in 10 mL of dimethylformamide (DMF, Fisher Scientific) at 0.1 M with 0.1 g of 10000 MW linear polyethylenimine (L-PEI, Sigma-Aldrich) and sonicated at 60 °C for 1 h to completely dissolve the polymer.…”
Section: Methodsmentioning
confidence: 99%
“…To address these limitations, a plasma‐based process known as plasma‐enhanced chemical film conversion (PECFC) has been developed and successfully used to obtain printable h‐BN at temperatures as low as 650°C on noncatalytic substrates. [ 138 ] The process involves the deposition of an ammonia borane precursor either by spin casting, spray coating, or inkjet printing, followed by atmospheric pressure DBD treatment in either Ar or a gas mixture of Ar and H 2 and simultaneous external heating of the substrate; a photo of an inkjet printed and converted film and its corresponding micro‐Raman spectral intensity map confirming h‐BN are shown in Figure 11a. Materials analysis showed that the crystallinity of the films grown by PECFC at 650°C are comparable to films grown by CVD on catalytic substrates at >1,000°C.…”
Section: Schemesmentioning
confidence: 99%
“…(b) Schematic diagrams of molybdenum disulfide (MoS 2 )‐based FET devices with and without plasma‐converted h‐BN layers (left) and corresponding I ds – V g transfer curves showing higher carrier mobility with h‐BN (right). (a and b) reprinted with permission from Liu et al [ 138 ] (c) Micro‐Raman spectra of MoS 2 films synthesized by thermal and plasma conversion at 500°C (left) and atomic force microscopy image of MoS 2 film synthesized by plasma conversion after a second thermal annealing step at 1,000°C, reprinted with permission from Liu et al [ 139 ] The spectra for the precursor before conversion is included for reference. The E 1 2g and A 1g peaks indicative of MoS 2 are only observed in the plasma‐converted film…”
Section: Schemesmentioning
confidence: 99%
“…[73][74][75] As long as the stable and homogeneous nanosheet ink is arranged (the ink applicability is judged by parameter Z, affected by ink viscosity, surface tension, density and nozzle diameter 76,77 ), the large-scale vdWHs arrays can be fabricated simply by printing the materials layer by layer through a printer. 78,79 A vertical Schottky barrier (SB) transistors array was successfully constructed in this way by printing indium−tin−oxide (ITO), indium−gallium−zinc−oxide (IGZO), reduced graphene oxide (rGO) and ion gel layer on a 4-in. Si wafer in sequence ( Figure 1E,F).…”
Section: F I G U R E 1 Schematic Illustration Of Four Key Strategies mentioning
confidence: 99%